Isolasi dan identifikasi bakteri dari susu kambing peranakan Ettawa (PE) terjangkit mastitis subklinis di Kemiri Kebo, Sleman, Yogyakarta - Widodo Suwito; Andriani Andriani; Widagdo Sri Nugroho (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2019)
Subclinical mastitis in Ettawa crosbreed goat (PE) is economic disease which lost milk yield that bacteria caused. The aim of these research was to isolatian and identification bacteria that caused subclinical mastitis in PE goat from Kemiri Kebo, Turi, Sleman, Yogyakarta. A total of 24 goat milk PE subclinical mastitis samples, were used in these research. Determination of subclinical mastitis in PE goat used CMT test which (++) and (+++) results. Isolation and identification conventional bacteria based on biochemical. Subclinical mastitis PE goat in Kemiri Kebo, Turi, Sleman, Yogyakarta was caused Staphylococcus intermedius (38%), Staphylococcus aureus (32%), Staphylococcus epidermidis (25%), Staphylococcus hycus (12%), Streptococcus sp (22%), Corynebacterium sp (12%), Pseudomonas aeruginosa (18%), and E. coli (2%). The research showed that Gram positive bacteria is dominant that caused subclinical mastitis in PE goat compared than Gram negative bacteria.